Optical coherence tomography based microangiography findings in hydroxychloroquine toxicity - Kam, Jason; Zhang, Qinqin; Lin, Jason; Liu, Jin; Wang, Ruikang K.; Rezaei, Kasra (Quantitative Imaging in Medicine and Surgery, 2016)
Optical coherence tomography based microangiography (OMAG) is a new, non-invasive imaging modality capable of providing three dimentional (3D) retinal and choroidal microvascular maps without a need for exogenous dye. In this study, we evaluated the retinal and choroidal microvascular architecture of the macula in a patient with hydroxychloroquine (HCQ) toxicity using OMAG. Detailed microvascular information of the retina and the underlying choroid showed loss of parafoveal outer retinal vasculature with sparing of the central fovea vasculature.